1 POLA PEMBERDAYAAN PEREMPUAN MELALUI PROGRAM KAMPUNG ORGANIK DALAM MENINGKATKAN KESEJAHTERAAN PEREMPUAN (Studi Kasus Paguyuban Perempuan Pengelola Sampah Terpadu Legok Makmur di Kelurahan Wates, Kecamatan Magelang Utara, Kota Magelang) - Paramitha, Dyah Ayu Risky; Setiyono, Budi (Journal of Politic and Government Studies, 2019)
Attempts for waste management needs participation from local peoples to managing it, especially from the housewifes, mainly because most of the waste comes from household waste. The Women's Association of Integrated Waste Management Legok Makmur (PPPST Legok Makmur) pioneering organic villages in Magelang City by inviting the housewifes to actively participate in processing waste into something useful. In this regards, this study aims to investigate the initial formation and activities, supporting factors and inhibitors and the positive and negative impacts of the existence of the Women's Association of Legok Makmur Integrated Waste Management. It also analyses the coordination with the regional government, and liberal feminism in the empowerment of the community. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observation, and document review. The data obtained is then analyzed by triangulating data sources.The results of this study shows that the process of forming the Legok Makmur Women's Association was stipulated by the amount of garbage in the polling station which makes the surrounding environment was dirty. This association has activities to process waste into compost, handicrafts, etc. with the sorting of organic and inorganic waste. The supporting factors are the presence of enthusiasm, peoples participation, and full commitment from the Government. While the inhibiting factors of people's awareness are low and the land area is still limited. The positive impact is that peoples become active, clean environment helps to get the Adipura Kencana Cup Award, and adds knowledge and no significant negative impact. The Legok Makmur Organic Village is cooperating with agencies such as the Environmental Agency of Magelang City and North Magelang District this Legok Makmur Organic Village is considered to make women autonomous as an economic function because they are aware of their role without forcing and make women become independent capable of being creative in waste management and can adds economic value.Key words : women empowerment, waste management, organic village